Answer:
3. y = 1
4. y = 3, x = 12
Explanation:
Like the question says, we'll be using substitution, so for the first one, we'll be substituting the value of x into the equation
x = 5
3x- 5y = 10
3 (5) - 5y = 10
15 - 5y = 10
5y = 15 - 10
5y = 5
y = 1
For the next one, it's a similar idea, except the value of x has the variable y in it, which is fine, as there is still only one value in the equation we'll be solving:
x = 4y
x + y = 5
4y + y = 5
5y = 15 (we needed to collect like terms to simplify)
y = 15/5
y = 3
we still have to find x, to this, we substitute the value of y into any of the equations:
x = 4y
x = 4 (3)
x = 12
Hope this helps,
Cate